Substâncias húmicas no metabolismo de nitrogênio em plantas de rúcula - Anjos, Olga Oliveira dos (2010)
Abundant research has demonstrated significant effects of humic substances of soil organic matter on plant growth and metabolism. Vermicompost, utilized for vegetable cultivation, has elevated concentrations of these substances. This research evaluates the effects of different doses of humic and fulvic acids extracted from vermicompost on the nitrogen metabolism of rucola plants grown in a greenhouse. Research was executed in Maranhão State University between August and October 2009. The experiment used 2,0 dm³ sized pots with washed sand as substrate, with the addition of nutritive solution every three days. Experimental layout was a bifactorial completely randomized block design with 2 acids in 5 doses and 5 replications each. The humic substances were extracted from approximately 500g of vermicompost based on their solubility in acids and bases, with doses of 0 (without HA and FA), 50, 100, 150 and 200 mg of C.L-1, applied at 10, 20 and 30 days after transplanting. I evaluated the aboveground dry weight, dry weight and volume of the roots, Nitrate Reductase activity, free amino-N, NO3-N, NH4-N, and protein-N in the leaves. Fulvic acids affected plant growth, whereas HA didn’t. 100 mg of C.L-1 as FA caused maximum increment of root mass, of root:shoot ratio and of total plant dry mass. Humic substances, especially the FA affected the nitrogen metabolism, especially by increasing nitrate reductase activity. These results suggest that small doses of fulvic acids are beneficial for an improved plant N uptake